Evald Ilyenkov on Freedom of Will - A.D. Maidansky (Культурно-историческая психология, 2024)
Evald Ilyenkov’s works explores the issue of free will within the framework of activity theory. According to him, the concept of freedom is linked to the general activity of living beings in the external world and to the purposeful nature of this activity. Human freedom, or the ‘freedom of the will’, is treated as acting in accordance with the “purpose of the species”, that is, the interests of human society. The will is a psychological function that subordinates an individual’s activity to the goals and norms of social life. Alternative doctrines postulate free will as an immediate “fact of consciousness”, discovered through introspection and underlying human activity. This is where traditional empirical psychology intersects with the physiological doctrine of the unconditional reflex of freedom. Ilyenkov regards such a conception of free will as a “psychological illusion” and examines the implications of this illusion in the classic experiments of academician Ivan Pavlov. The article offers a cultural-historical perspective on the development of the human mind as a process of increasing free will: the emancipation of mental activity from the captivity of natural affects through the use of cultural tools and man’s rational understanding of the world and himself.